Determining counselling communication strategies associated with successful quits in the National Health Service community pharmacy Stop Smoking programme in East London: a focused ethnography using recorded consultations. Issue 10 (27th October 2017) - Rivas, Carol; Sohanpal, Ratna; MacNeill, Virginia; Steed, Liz; Edwards, Elizabeth; Antao, Laurence; Griffiths, Chris; Eldridge, Sandra; Taylor, Stephanie; Walton, Robert
Abstract : Objectives: To determine communication strategies associated with smoking cessation in the National Health Service community pharmacy Stop Smoking programme. Setting: 11 community pharmacies in three inner east London boroughs. Participants: 9 stop smoking advisers and 16 pairs of smokers who either quit or did not quit at 4 weeks, matched on gender, ethnicity, age and smoking intensity. Method: 1–3 audio-recorded consultations between an adviser and each pair member over 5–6 weeks were analysed using a mixed-method approach. First a content analysis was based on deductive coding drawn from a theme-oriented discourse analysis approach and the Roter Interaction Analysis System. Core themes were identified through this quantification to explore in detail the qualitative differences and similarities between quitters and non-quitters. Results: Quantitative analysis revealed advisers used a core set of counselling strategies that privileged the 'voice of medicine' and often omitted explicit motivational interviewing. Smokers tended to quit when these core strategies were augmented by supportive talk, clear permission for smokers to seek additional support from the adviser between consultations, encouragement for smokers to use willpower. The thematic analysis highlighted the choices made by advisers as to which strategies to adopt and the impacts on smokers. The first theme 'Negotiating the smoker–adviser relationship' referred to adviser judgements about the likelihood the smoker would quit. The second theme, 'Roles of the adviser and smoker in the quit attempt', focused on advisers' counselling strategies, while the third theme, 'Smoker and adviser misalignment on reasons for smoking, relapsing and quitting', concerned inconsistencies in the implementation of National Centre for Smoking Cessation and Training recommendations. Discussion: Advisers in community pharmacies should use the advantages of their familiarity with smokers to ensure appropriate delivery of patient-centred counselling strategies and reflect on the impact on their counselling of early judgements of smoker success.